MORE THAN JUST A FOLKTALE: REVITALIZING THE VALUES OF POASA-ASA AND POHAMBA-HAMBA FOR MODERN CHARACTER EDUCATION - La Doni; Hartinawanti Hartinawanti (JURNAL NALAR PENDIDIKAN, 2025)
This research aims to describe how the application of Poasa-asa and Pohamba-hamba values is reflected in the daily lives of elementary school students, as depicted in the local folktale of Ence Sulaiman. This research uses a descriptive qualitative design. The subjects of this study are students of SDN 2 Wanci. Data were collected through observation, document studies, and interviews. The data were analyzed to identify patterns of value application in student behavior and activities. The findings reveal five main aspects of the application of Poasa-asa and Pohamba-hamba values among students: (1) Students cooperate to maintain school cleanliness, show empathy and encouragement, and teach fair play. (2) Students help their classmates when they face difficulties in completing school assignments. (3) Students give love cards to their loved ones (parents, siblings, peers, and others). (4) Students donate clothes that are still wearable in accordance with the teachings of Islam, which encourage us to care for others. (5) Students mention the names of people they want to pray for, such as friends and family.